THE CHARACTERISTICS OF PSEUDO-RELIGION: A Case Study of the Documentary Film In the Name of God - A Holy Betrayal - Bonnarty Steven Silalahi (QUAERENS: Journal of Theology and Christianity Studies, 2023)
The documentary film "In the Name of God: The Holy Betrayal" records interviews with former followers of four sects in South Korea, namely Jesus Morning Star/Jeong Myeong-seok, Five Oceans, Baby Garden, and Manmin Central Church. Through a case study, five similarities were found among these sects, namely individual cult (worshiping their leaders), religious fraud (misuse of money), religious abuse (exploitation to sexual harassment), isolation and exclusivism, and extreme mysticism. These five similarities are covered by a fanaticism that makes followers not question or criticize teachings, even if they are contrary to the law. Through a literature review of the cases in this documentary, this research concludes that these five similarities are part of the sect's character. This analysis has significance for introducing Christian movements and tendencies for teachings to become pseudo-religions. Film dokumenter “In the Name of God: The Holy Betrayal” merekam wawancara dari mantan pengikut empat sekte di Korea Selatan, yakni Jesus Morning Star/ Jeong Myeong-seok, Five Oceans, Baby Garden dan Manmin Central Church. Melalui studi kasus yang dilakukan, ditemukan lima kesamaan sekte ini, yakni kultus individual (menuhankan pemimpinnya), religious fraud (penyalahgunaan uang), religious abuse (eksploitasi hingga pelecehan seksual), isolasi dan eksklusifisme serta mistisisme ekstrim. Kelima kesamaan ini ditambah dengan sikap fanatisme yang membuat pengikutnya tidak mempertanyakan atau melakukan kritik terhadap ajaran-ajaran, meskipun itu bertentangan dengan hukum. Melalui studi pustaka atas kasus-kasus dalam dokumenter ini, penelitian ini menyimpulkan bahwa kelima kesamaan tersebut adalah sebagian dari karakter sekte. Analisis ini memiliki signifikansi bagi pengenalan gerakan Kekristenan dan kecenderungan ajaran menjadi agama semu.